Epidemiological data on cervical carcinoma relevant to cytopathology - C. La Vecchia; A. Decarli; G. Gallus (1987)
Epidemiological studies based on cervical cytopathology have aroused widespread interest since it was realized that they could be a useful tool for measuring the effectiveness of screening programs and defining practical measures for the prevention of invasive neoplasms and deaths. In the present article, published evidence from screening programs, cohort investigations and case-control studies is reviewed, and possibilities for further analyses and applications are discussed. In particular, when estimates of the relative protections conveyed by Pap smear from various case-control studies conducted on different populations and using different criteria of selection were pooled, a surprisingly close concordance emerged, with overall risk estimates of invasive cervical cancer of 0.42 for women reporting one smear, and of 0.20 for two or more smears in the past. This protection appeared to be long-lasting in a considerable proportion of cases, since the major determinant of invasive cancer risk was the number of previous smears rather than the interval since last smear, and a noticeable residual effect was evident even more than 10 years after the last smear. Besides providing a measure of the effectiveness of cytological screening and helping define the optimal frequency of screening using the limited resources available, case-control studies should permit accurate estimates of the sensitivity of the test and quantify the probability of transition and the duration of various stages of the neoplastic process, i.e., permit a better understanding of the natural history of the disease.